Trans identités : genres pluriel.le.s : acceuil, droits, santé, jeunesse, emploi... tous tes bien informé.e.s. - Dufrasne, Aurore; Nisol, Max; Pire, Maêl (Bruxelles : Genres Pluriels, 2016)
Fonds Suzan Daniel (FSD)
Frans
Monografie